An Examination of Race Strategies in NCAA Cross Country Championship Events - Peter S Finley; Jeffrey J Fountain (Journal of Coaching and Sports Science, 2023)
This research sought to evaluate race strategies in Cross Country running to determine whether a fast, predicted, or slow start would yield the best results when coupled with an advancing or regressing strategy from the 1st checkpoint through to the finish. Twelve National Collegiate Athletic Association (NCAA) Championship races were analyzed from 2021 to 2022 (N=315 teams; 2,205 runners). Success was defined by each team's finish relative to their anticipated finish, as determined through pre-championship national rankings. Results indicated that starting well ahead of a predicted finishing place and advancing throughout the race can yield finishes well ahead of a team's ranking. Still, less than 5 percent of teams could employ that strategy. A more likely positive result came from a conservative start, coupled with consistently advancing through the field for the remainder of the race, as nearly 14 percent of teams could employ that strategy. Starting a race slowly did not typically lead to success, even if a team consistently advanced through the field after the 1st checkpoint. Teams that regressed throughout the race were not likely to have a successful race.